2015
DOI: 10.14569/ijacsa.2015.060910
|View full text |Cite
|
Sign up to set email alerts
|

Developing Computer Network Based on EIGRP Performance Comparison and OSPF

Abstract: Abstract-One of the computer network systems technologies that are growing rapidly at this time is internet. In building the networks, a routing mechanism is needed to integrate the entire computer with a high degree of flexibility. Routing is a major part in giving a performance to the network.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
1
0
2
Order By: Relevance
“…Dalam struktur jaringan ini, perangkat yang berperan penting adalah router, yang mengatur alur data dari komputer pengirim ke komputer penerima. Router ini dapat diatur melalui program untuk mengawasi aliran data dari semua komputer yang terhubung [1].…”
Section: Pendahuluanunclassified
“…Dalam struktur jaringan ini, perangkat yang berperan penting adalah router, yang mengatur alur data dari komputer pengirim ke komputer penerima. Router ini dapat diatur melalui program untuk mengawasi aliran data dari semua komputer yang terhubung [1].…”
Section: Pendahuluanunclassified
“…Fokus penelitian ini adalah pada routing dinamis. Dalam routing dinamis, terdapat perkembangan teknologi protokol yang digunakan, seperti Routing Information Protocol (RIP), Interior Gateway Routing Protocol (IGRP), Open Shortest Path First (OSPF), Enhanced Interior Gateway Routing Protocol (EIGRP), dan Border Gateway Protocol (BGP) [3].…”
Section: Pendahuluanunclassified
“…Mardedi and Rosidi presented the analysis and comparison of performance between EIGRP and OSPF based on Cisco Packet Tracer 6.0.1. They found that EIGRP is better than OSPF in terms of delay and convergence time [9]. Whitfield and Zhu compared the performance of OSPFv3 and EIGRPv6 by using real Cisco hardware in experiments.…”
Section: Related Workmentioning
confidence: 99%